2017
DOI: 10.1039/c7ra02141k
|View full text |Cite
|
Sign up to set email alerts
|

Influence of support on the catalytic properties of Pt–Sn–K/θ-Al2O3 for propane dehydrogenation

Abstract: The correlation between the physicochemical parameters of the catalysts and the dehydrogenation performance of propane was established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The elemental line scan in Figure 6 shows high Pt distribution throughout the Mg-doped catalyst (not an eggshell type) as opposed to the surface dispersion of Pt shown in Table 3. [33][34][35][36]. Values for the acidity of supports and catalysts, determined by NH 3 -TPD, are tabulated in Table 4.…”
Section: Co Pulse Chemisorptionmentioning
confidence: 99%
“…The elemental line scan in Figure 6 shows high Pt distribution throughout the Mg-doped catalyst (not an eggshell type) as opposed to the surface dispersion of Pt shown in Table 3. [33][34][35][36]. Values for the acidity of supports and catalysts, determined by NH 3 -TPD, are tabulated in Table 4.…”
Section: Co Pulse Chemisorptionmentioning
confidence: 99%
“…et al [30]. Generally, the metallic state of Sn acts as a poisoning agent and Sn(II.IV) serves as promotor in the catalyst [1,33].…”
Section: Xps Analysismentioning
confidence: 99%
“…The temperature programmed oxidation profile (TPO) based on the coke removal rate is presented in Figure 8c for the NaBH 4 reduced catalyst and Figure 8d for the hydrogen reduced catalyst. It was reported that the complete combustion of coke will happen under 400 • C in air atmosphere [1]. From Figure 8a,b, it can be noted that the complete combustion of coke deposited on both catalysts happened below 400 • C. Only one peak was observed during the differential thermal analysis of both spent catalysts, as shown in Figure 8c,d, between 200 • C and 320 • C. The exothermic peak between 200 • C and 320 • C represents the carbon deposition on the metal surface, which is the result of the catalyzing effect of metal towards oxidation of coke deposited on it [13,25,34].…”
Section: Tga Analysis Of Coke Deposition On Spent Catalystsmentioning
confidence: 99%
See 2 more Smart Citations